KEWAJIBAN PEMBAYARAN ATAS PELIMPAHAN UTANG PAJAK PEWARIS KEPADA AHLI WARIS DIPANDANG DARI ASPEK HUKUM PERDATA - Kusumo, Vonny Kristanti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Taxes are the biggest source of state revenue in financing the budget related to development and state interests. The Directorate General of Taxes (DGT) is an institution that is given coercive powers for the benefit of state revenues originating from taxes, which has the duty and authority to manage state revenues originating from tax collections and has the goal that tax collection can run properly and effectively so that can facilitate the needs of the country's development. Unfortunately there are too many regulations in the field of taxation that are enforced and changes are very dynamic, so that taxes become something that is not understood by the public as taxpayers who are also tax subjects. Ignorance of taxpayers often harms them in the event of a tax debt overflow. And because the tax rules are very numerous, complicated and very dynamic, making taxpayer losses increase due to their negligence in understanding tax regulations. If a Taxpayer has ever had a tax debt that has not been paid during his life, then when the Taxpayer dies, the Government does not consider the tax debt paid off and the tax collection is still valid. This study uses a normative juridical research method, with a statutory approach based on primary and secondary legal materials.